2007
DOI: 10.1093/eurheartj/ehl488
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combined antiplatelet-warfarin therapy after coronary stenting

Abstract: Our study shows that the prognosis is unsatisfactory in warfarin-treated patients irrespective of the drug combination used. Aspirin plus warfarin combination seems to be inadequate to prevent stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
1
20

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(206 citation statements)
references
References 28 publications
6
179
1
20
Order By: Relevance
“…[1][2][3] Oral anticoagulation therapy with vitamin K antagonists reduces the incidence of recurrent ischemic events after myocardial infarction but also increases the risk of bleeding when it is added to aspirin or aspirin and clopidogrel. [4][5][6][7][8][9] Apixaban, an orally active, selective, direct factor Xa inhibitor, has been shown to reduce the incidence of venous thromboembolism in patients undergoing orthopedic surgery and to prevent thromboembolic events in patients with atrial fibrillation who are not candidates for oral vitamin K antagonist therapy. [10][11][12][13][14][15] We previously studied the use of apixaban, at doses of 5 to 20 mg daily, in patients who had had recent acute coronary syndromes and who were receiving aspirin or aspirin plus clopidogrel.…”
mentioning
confidence: 99%
“…[1][2][3] Oral anticoagulation therapy with vitamin K antagonists reduces the incidence of recurrent ischemic events after myocardial infarction but also increases the risk of bleeding when it is added to aspirin or aspirin and clopidogrel. [4][5][6][7][8][9] Apixaban, an orally active, selective, direct factor Xa inhibitor, has been shown to reduce the incidence of venous thromboembolism in patients undergoing orthopedic surgery and to prevent thromboembolic events in patients with atrial fibrillation who are not candidates for oral vitamin K antagonist therapy. [10][11][12][13][14][15] We previously studied the use of apixaban, at doses of 5 to 20 mg daily, in patients who had had recent acute coronary syndromes and who were receiving aspirin or aspirin plus clopidogrel.…”
mentioning
confidence: 99%
“…From 625 initial citations, 16 eligible studies including a total of 9185 patients were identified in the present meta‐analysis,4, 5, 6, 7, 12, 14, 15, 19, 20, 21, 22, 23, 24, 25, 26, 27 with 5680 patients in the triple therapy group and 3505 in the dual therapy group (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies were identified in the DAPT subgroup,4, 5, 6, 7, 19, 20, 21, 22, 23, 24, 25, 26 with the other 4 studies included in the OAC/C subgroup 12, 14, 15, 27…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, because blockade of P2Y 12 receptor–mediated signaling with clopidogrel is associated with greater platelet‐inhibitory effects than cyclooxygenase‐1 inhibition with aspirin, as well as the established role of P2Y 12 receptor blockade on recurrent thrombotic events, clopidogrel might be expected to be more effective than aspirin at reducing risk of ST, with a potentially lower rate of gastrointestinal bleeding as well 40. A few retrospective cohorts have observed a lower incidence of ST with clopidogrel plus warfarin dual antithrombotic therapy,13, 20, 41 and clopidogrel, aspirin, and warfarin triple antithrombotic therapy,42 compared with warfarin and aspirin dual antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%